DIAGNOSTIC CRITERIA AND A PROGNOSTIC MODEL FOR THE COURSE OF SOFT TISSUE NECROBIOTIC INFECTIONS IN DIABETES PATIENTS BASED ON ARTIFICIAL INTELLIGENCE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Expanding the model using artificial intelligence technologies has transformed the scale into a dynamic system adaptable to the characteristics of each patient and based on a wide array of accumulated data.